A Qualitative Exploration of Self-Kindness and “Treating Oneself” in Contexts of Eating, Weight Regulation and Other Health Behaviors: Implications for Mindfulness-Based Eating Programs - Egan, Helen; Mantzios, Michail (Frontiers in Psychology, 2018)
Background: Caring for oneself through mindfulness and compassion to improve or enhance health behaviours, and specifically eating behaviours has come to the forefront of scientific inquiry. The experiences and challenges for people in decision making around food within the context of self-kindness for body and mind care have not been previously explored. Aims: This study explored the experiences of eating behaviours in a community sample and examined the understanding of self-kindness and its relationship to eating behaviours and wellbeing of body and mind. Methods: A phenomenological theoretical position was taken; data were collected using individual semi-structured interviews. The sample was twenty-five members of the wider community in the West Midlands in England. The data were analysed using Braun and Clarke’s (2006) procedural steps for thematic analysis. Results: Two overarching themes were inductively formulated: ‘Thinking about eating’ and ‘Caring for body and mind’. Five themes were constructed: (a) Treat food is exceptional eating, (b) The proof of the pudding is in the planning, (c) Dieting is a dirty word, which are subsumed under Thinking about eating, and (d) Self-kindness is a disavowed abstract noun, and (e) Self-kindness: A rose by any other name; under Caring for body and mind. Participants described a number of ways of treating themselves both with food and with other activities and pleasure in eating was discussed in terms of social aspects of eating rather than food. Two clear contradictions within narratives around eating and health behaviours were shown. Participants largely eschewed the concept of dieting, but described engaging in highly regulated and restrained eating. There was a lack of connection with the notion of self-kindness; although positive eating and exercise health behaviours were undertaken, they were described as necessary self-regulation, not construed as acts of self-kindness. Conclusions: The results suggests a lack of ease in the interpretation of being kind to oneself as a means of improving mental wellbeing, and an inability to relate self-kindness to physical health behaviours. The association of self-kindness with self-indulgence, and the described disconnect between hunger, satiety and pleasure in eating has implications for interpretation of mindful eating scales, practices and